Energia digestível para larvas de tilápia-do-nilo (oreochromis niloticus) na fase de reversão sexual - Boscolo, Wilson Rogério (2005)
This experiment was conducted to evaluate different levels of digestible energy on the performance of Nile tilapia larvae (Oreochromis niloticus) during the sexual reversion phase. Three hundred and seventy-five larvae with initial average length and weight of 21.0±4.0 mg and 1.19±0.72 cm, respectively, were allotted to 25 30L-aquarium. A completely randomized design with five treatments and five replicates was used. The aquarium with 15 larvae was the experimental unit. The diets were formulated to contain levels of 3,300, 3,525, 3,750, 3,975, and 4,200 kcal/kg of digestible energy and to be isoprotein (38.6% digestible protein). The animals were fed ad libitum five times a day. At the end of the experiment, the averages of weight (PF), survival rate (SO), condition factor (FC) and length (CF) were analyzed. Linear reduction of fishes PF and CF, as the dietary digestible energy levels increased, was observed. No differences on fish SO and FC of different treatments were observed. Deleterious effects on performance due to the increasing dietary digestible energy levels were noticed for Nile tilapia larvae during the sexual reversion.